Explanatory Factor Analysis of Critical Thinking Instrument for Elementary Students - Muhammad Febrian Adi Guna; Sahal Abdullah; Muhamad Azlan Al Disa (CV. Akademi Merdeka, 2025)
One of the main challenges in primary education is the low critical thinking skills of students during the learning process, which has a major impact on their academic achievement as well as their social and emotional development. This study aims to analyze the structure of the instrument factors for measuring critical thinking ability, which is developed based on four main dimensions: analytical ability, evaluation ability, inference ability, and problem-solving skills in elementary school students. This study uses a quantitative approach with a survey design involving 240 elementary school students. Data analysis was carried out through Explanatory Factor Analysis (EFA). The findings show that the four dimensions of critical thinking have significant factor weight, adequate convergent validity, and high construct reliability, as well as SRMR values that have a match with empirical data. The model created can describe well and in context how critical thinking works as a whole. This instrument is relevant for academic research as well as a diagnostic tool for teachers in designing responsive learning. These findings contribute significantly to improving the quality of basic education through a comprehensive and effective evaluation of students' critical thinking skills.